COMPREHENSIVE PUBLIC SMOKING PROGRAM LEGISLATIVE STRATEGIES (Tufts Archival Research Center, 2007)
MARGINALIA; Confidential; Report on Legislative strategies for the comprehensive public smoking program. Lists strategies by lobbying efforts against smoking restrictions, ventilation legislation, smoker's rights legislation, and lists for targets. Includes proposed budget for these programs.